Sedation in Japanese dental schools. - Morse, Zac (2004)
There is very little information about the practice of sedation in Japan. Despite the remarkable advances in dentistry, fear and anxiety continue to be significant deterrents for seeking dental services. Most dental procedures can fortunately be undertaken with the aid of sedation. A comprehensive survey of all the dental schools in Japan was carried out to determine what sedation practices were used in Japan. All 29 dental schools in Japan possessed a dedicated department of anesthesiology at the time of this survey. The survey attempted to determine the specific sedation methods (techniques, routes of administration, and agents used in sedation) as well as practices (monitoring, fasting, location, education, and fees involved in sedation). The results indicate that there was a broad range in sedation practices. The Japanese Dental Society of Anesthesiology may wish to examine the findings of this study and may wish to formulate guidelines appropriate for the practice of sedation in Japan. Others may also wish to compare their own practices with those of Japan.